Distinct Microrna Expression Pattern in Breast Cancer Cells Following Anti-neoplastic Treatment: A Systematic Review and Functional Analysis of Microrna Target Genes - Derani Qatrun Nada; Muhammad Lasim Masniza; Marjanu Hikmah Elias; Abdul Rahman Hayati; Adila Abdul Hamid; Natasya Abdullah; Marlini Muhamad; Siva Gowri a/p Pathmanathan; Fadlul Azim Fauzi Mansur; Nur Fariha Mohd Manzor (College of Pathologists, Academy of Medicine Malaysia, 2024)
Indexed by Scopus/MyCite